Cover Crop Benefits for South Florida Commercial Vegetable Producers - Qingren Wang; Yuncong Li; Edward A. Hanlon; Waldemar Klassen; Teresa Olczyk; Ikechukwu V. Ezenwa (EDIS)
This article describes how and why to use cover crops in South Florida vegetable production systems, and identifies several cover crops that work in Florida's climate, that contribute to nutrient conservation, and whose biomass can be incorporated to improve soil organic matter. Updated October 2018.